Commodity Transport Studies—Summary Volume I - Planning Commission (Planning Commission, 1968)
The largest consumers of limestone in India are the cement plants, the next major consumer being the iron and steel industry. There is no fixed specification of limestone required for cement manufacture, except that only small percentages of magnesium carbonate, free silica, alkalise and sulphides are tolerable. In the iron and steel industry limestone is required in two grades, one for fluxing in the blast furnace (BF Grade) and the other for fettling in the steel melting shops (SMS Grade). The total consumption of limestone, by the Iron and Steel Industry is about 0.5 tonne for every tonne of steel produced.
Planning Commission
Planning Commission